Photon-generated carriers excite superoxide species inducing long-term photoluminescence enhancement of MAPbI3 perovskite single crystals. Issue 24 (31st May 2017) - Feng, Xiyuan; Su, Huimin; Wu, Yinghui; Wu, Han; Xie, Jian; Liu, Xinke; Fan, Jin; Dai, Junfeng; He, Zhubing
Abstract : Superoxides, produced by the reaction of O2 with photon-generated electrons, with the assistance of iodine vacancies and lead ions, lead to photoluminescence enhancements in perovskites. Abstract : It is always essential for the design and optimization of devices to discover the interaction mechanism of light with hybrid perovskite materials in air. However, the mechanism is currently still under debate, although there is already a consensus that oxygen gas molecules along with light irradiation contribute predominantly to photoluminescence (PL) enhancements in perovskite crystals. In this work, we measured the light intensity, excitation energy, oxygen environment and depth dependence of the photoluminescence (PL) enhancements in perovskite single crystals by using confocal fluorescence microscopy. The dependence of the PL enhancement on the excitation energy and environment explicitly indicates the indispensable roles of photon-generated carriers and oxygen gas molecules. Moreover, the PL enhancement depth of over 100 μm in an oxygen environment demonstrates that the penetration of oxygen species must be the dominant mechanism, rather than their diffusion. Furthermore, the passivation of the oxygen species occurs in a stable and long-term manner, even in the absence of light, in contrast to that of carriers and neutral species. On the basis of these solid data, we propose that the O2 − superoxides yielded from the reaction of O2 with free-moving electrons are responsible for the related PL enhancement effect involved in our work and other literature reports. This paper will definitely deepen our understanding of the interaction mechanism in this field.